Transnational transformations: coupling migration and change - van Houte, M (International Migration Institute, 2016)
In this paper, I propose an analytical framework to study the dual relationship between migration and change, addressing a two-fold question: what are the consequences of political developments on migration and transnational engagement, and what are the consequences of migration and transnational engagement on politics in the country of origin? I introduce two sets of theoretical debates that have dealt with the relationship between migration and change as building blocks to develop an actor-oriented analytical framework to study both outcomes and processes of becoming a migrant and transnationally active. The framework addresses the need in the migration and development debate to understand the heterogeneity of both processes, that allows us to see migration, integration and transnational engagement as different outcomes of these processes from above and below, while avoiding a loss of analytical focus. This framework has four main analytical benefits. First, the framework allows us to analytically disentangle the different dimensions of change, but also to study the process by which migrants become active agents of change, rather than essentialising this as fixed or static. Second, the cyclical structure of the framework addresses the need in the migration and development debate to understand migration and change as dynamic processes that are both steered from below and from above in an interactive process that changes over time and on all levels. Third, the interactions in the framework allow us to understand the heterogeneity of mechanisms and outcomes of migration-induced change (Burgess 2012). It highlights that migration-induced change is not necessarily democratisation and not always for the better (Portes 2009). Fourth, the framework allows for hypotheses on processes and outcomes of migration and change that centralises time and mobility in addition to spatial factors.